Fetal Cortical Plate Segmentation Using Fully Convolutional Networks With Multiple Plane Aggregation - Hong, Jinwoo; Yun, Hyuk Jin; Park, Gilsoon; Kim, Seonggyu; Laurentys, Cynthia T.; Siqueira, Leticia C.; Tarui, Tomo; Rollins, Caitlin K.; Ortinau, Cynthia M.; Grant, P. Ellen; Lee, Jong-Min; Im, Kiho (Frontiers in Neuroscience, 2020)
Fetal magnetic resonance imaging (MRI) has the potential to advance our understanding of human brain development by providing quantitative information of cortical plate (CP) development in vivo. However, for a reliable quantitative analysis of cortical volume and sulcal folding, accurate and automated segmentation of the CP is crucial. In this study, we propose a fully convolutional neural network for the automatic segmentation of the CP. We developed a novel hybrid loss function to improve the segmentation accuracy and adopted multi-view (axial, coronal, and sagittal) aggregation using a test-time augmentation method to reduce errors caused by a single prediction, enabling the use of three-dimensional (3D) information. We evaluated our proposed method using the ten-fold cross-validation of 52 fetal brain MR images (22.9–31.4 weeks of gestation). The proposed method obtained Dice coefficients of 0.907 ± 0.027 and 0.906 ± 0.031 as well as a mean surface distance error of 0.182 ± 0.058 mm and 0.185 ± 0.069 mm for the left and right CPs, respectively. In addition, the left and right CP volumes, surface area, and global mean curvature generated by automatic segmentation showed a high correlation with the values generated by manual segmentation (R2 > 0.941). We also demonstrated that the proposed hybrid loss function and the combination of multi-view aggregation and test-time augmentation significantly improved the CP segmentation accuracy. Our proposed segmentation method will be useful for the automatic and reliable quantification of the cortical structure in the fetal brain.